2018
DOI: 10.3390/f9040160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tree Species for Biomass Energy Production in Northwest Spain

Abstract: Three types of forest stands (chestnut coppice, maritime pine stands, and poplar and willow short-rotation woody crops (SRWC)) were evaluated to determine their potential for energy production. The properties of the main aboveground biomass fractions (wood, bark and crown) and also the whole tree were analysed, thus providing data that could be used for management purposes and for evaluating potential forest, biomass energy yields and atmospheric emissions. Proximate, elemental and energetic analyses of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 34 publications
10
50
0
1
Order By: Relevance
“…This is in conformity with what was reported on woods and barks of some biomass by Deka, et al [9] and Nosek, et al [13]. Different studies have demonstrated the influence of moisture content on the combustion properties of fuelwood materials [24][25][26][27][28] and concluded that moisture had negative effect on fuel value of the wood. Thus, bio fuel materials with low moisture content are always preferred because of the high energy content per unit volume, durability and slow burning rate.…”
Section: Moisture Content (Mc)supporting
confidence: 90%
See 3 more Smart Citations
“…This is in conformity with what was reported on woods and barks of some biomass by Deka, et al [9] and Nosek, et al [13]. Different studies have demonstrated the influence of moisture content on the combustion properties of fuelwood materials [24][25][26][27][28] and concluded that moisture had negative effect on fuel value of the wood. Thus, bio fuel materials with low moisture content are always preferred because of the high energy content per unit volume, durability and slow burning rate.…”
Section: Moisture Content (Mc)supporting
confidence: 90%
“…Among the trees, FC content ranged from 24.19% in C. arereh to 36.20% in P. reticulatum (Table 6). This is similar to those recorded for some indigenous tree species by Deka, et al [9] but higher than the range of 13.50 to 23.02% obtained in some tree species by Álvarez-Álvarez, et al [24] and 5.1 to 7.6% obtained in the stump of some trees from short rotation forest by Senelwa and Sims [8]. On the average, FC content is approximately 15% higher in tree bark compared to their respective wood without bark.…”
Section: Percentage Fixed Carbonsupporting
confidence: 88%
See 2 more Smart Citations
“…In the fifth column of Table 2, the ash content ranges from 0.994 (Olea africana) to 4.445 (Acokanthera schimperi). According to Álvarez-Álvarez et al [21], the tree species with the highest fixed carbon hold up the least ash content. Similar observations are found in this research.…”
Section: The Ash Contentmentioning
confidence: 99%